2022
DOI: 10.1186/s12967-022-03673-4
|View full text |Cite
|
Sign up to set email alerts
|

LPAR5 confers radioresistance to cancer cells associated with EMT activation via the ERK/Snail pathway

Abstract: Background Epithelial-to-mesenchymal transition (EMT) is a critical event contributing to more aggressive phenotypes in cancer cells. EMT is frequently activated in radiation-targeted cells during the course of radiotherapy, which often endows cancers with acquired radioresistance. However, the upstream molecules driving the signaling pathways of radiation-induced EMT have not been fully delineated. Methods In this study, RNA-seq-based transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…LPAR5 has recently been reported to be overexpressed in NSCLC [55] and knocking it out in A549 cells has been shown to inhibit apoptosis and oppose growth arrest following irradiation [56]. LPAR5 upregulation, therefore, offers a credible mechanistic justification for increased survival and less pronounced G2 arrest seen after irradiation of A549 cells under hypoxia in our experiments.…”
Section: Lpar5mentioning
confidence: 50%
“…LPAR5 has recently been reported to be overexpressed in NSCLC [55] and knocking it out in A549 cells has been shown to inhibit apoptosis and oppose growth arrest following irradiation [56]. LPAR5 upregulation, therefore, offers a credible mechanistic justification for increased survival and less pronounced G2 arrest seen after irradiation of A549 cells under hypoxia in our experiments.…”
Section: Lpar5mentioning
confidence: 50%
“…Additionally, a series of observations underscore the involvement of growth-related pathways, including PI3K/AKT and MAP cascades, in the regulation of ERα activity. Moreover, the role of ERα itself has been implicated in the regulation of cellular radioresistance (58,70,71). Further studies are required for the explanation of the mechanism of the inactivation of ERα by DNA damage agents and how DNA damage inhibits ERα transcription without affecting its expression.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is a specific cytokine that induces extracellular matrix production [ 39 , 40 ], consistent with our findings. TGF-β promote radiation-induced EMT process [ 41 , 42 ] Nevertheless, the relationship between TLRs and EMT is not well understood. This study revealed that MPLA promotes the polarization of RAW 264.7 cells towards the M1 phenotype and inhibits TGF-β secretion by macrophages.…”
Section: Discussionmentioning
confidence: 99%